A systematic review of direct preference measurements in health states treated with plastic surgery. Issue 3 (1st June 2022) - Hansson, Emma; Sandman, Lars; Davidson, Thomas
Abstract: One way to compare health care needs and outcomes on common scales is by estimating the strength of preferences or willingness-to-pay (WTP). The aim of this study was to review directly measured preference values and WTP estimates for health states treated by plastic surgery. The included articles had to meet the criteria defined in the SPIDER (Sample, Phenomenon of Interest, Design, Evaluation, Research type). Relevant databases were searched using predetermined strings. Data were extracted in a standardised manner. Included studies were appraised according to the Grading of Recommendations Assessment, Development, and Evaluation (GRADE) approach for rating the importance of outcomes. In total, 213 abstracts were retrieved. Of these, 179 did not meet the inclusion criteria and were excluded, leaving 34 studies in the review. The risk of bias was considered moderate in four studies and serious in the rest. The overall certainty of evidence for directly measured preference values and WTP estimates for health states treated by plastic surgery is low (Grade ƟƟОО). The lowest preference scores were generally elicited for facial defects/anomalies and the highest for excess skin after massive weight loss. Scientific knowledge about preferences and the resulting health gains might play an essential role in deciding which procedures should be considered for public funding or rather rationed within the system. Better quality studies are required to allow for such applications.